Cadmium chalcogenide thin films - Ho, Soon Min (2015)
Cadmium chalcogenide thin films have been prepared by many deposition methods. The main benefit of cadmium chalcogenide materials is produce high power conversion efficiency solar cells compared with other chalcogenide thin films. Unfortunately, cadmium is highly toxicity and non-eco-friendly substance. Therefore, researchers must work harder in order to seek the less toxic materials to replace cadmium.